Psychiatric nursing : contemporary practice - Boyd, Mary Ann (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
Based on the biopsychosocial model of psychiatric nursing, this text provides coverage of mental health promotion, assessment, and interventions in adults, families, children, adolescents, and older adults